A proposed collection development policy for the Gender and Development Library of the Philippine Broadcasting Services - Dela Cruz, Jose A. Jr.; Lapuz, Elvira B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The Philippine Broadcasting Service - Bureau of Broadcast Services (PBS-BBS) is the official radio broadcast arm of the Philippine government. The PBS-BBS) is the official radio broadcast arm of the Philippine government. The PBS-BBS established the Gender and development (GAD) Library to be able to recognize the role of women in the development of the nation. With the early establishment of the library it seems that the library has its weaknesses to address.
The objectives of the study are the following: 1) to determine the status of the Gender and Development Library as determined by user needs analysis and financial analysis; 2) to determine the assessment of the library based on technical analysis; 3) to determine the status of the staffing pattern in the library; and 4) to determine the recommendations that can be made to have a strong collection development policy and strategic plan in the library.
This study is descriptive in nature and evaluative methods were also employed for the research study. The research design involves careful selection of subjects, the use of research instruments, well-planned strategy of gathering data and systematic presentation, analysis and interpretation of the meaning and significance of what is described. The respondents are the head of the Research Division of PBS-BBS, the GAD librarian and the rest of the library staff, as well as their library users. In determining the sample population, convenience sampling method was used. In this study 70 employees participated in this survey.
The study concludes that the library is not organized and mismanaged because the librarian does not practice or is not able to practice all aspects/components in managing the library. Aside from the librarian concerned was asked by the head of the Philippine Broadcasting - Bureau of Broadcast Services (PBS-BBS) to do clerical works most of the time. With that, we won't be surprised if the library was left unmanaged.
The study recommends the following: 1) The Gender and Development Library must be provided with adequate and continuing budgetary support as a separate item from the budget of the parent organization where it belongs; 2) the Gender and Development Library must be an independent unit of the parent organization to which it belongs and be managed under the direct jurisdiction of a qualified librarian.; 3) Being a special library, the Gender and Development Library can improve on its collection by including information on employees and sponsors. The librarian's input or value added may be done by including print and non-print types and forms and materials.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Philippine Broadcasting Service-Bureau of Broadcasting Services (PBS-BBS).; Gender and development (GAD) library -- Information services -- Use studies; Gender and development (GAD) library -- Information resources -- Use studies; Collection development (libraries) -- Policy statements